LEARNING OUTCOMES BASED ON MYERS-BRIGGS TYPE INDICATOR (MBTI) PERSONALITY FROM ACCOUNTING DEPARTMENT STUDENTS SAM RATULANGI UNIVERSITY - Olivia Sardjono (ACCOUNTABILITY, 2023)
This study aims to give the Myers-Briggs Type Indicator (MBTI) test to students of the Accounting Department at Sam Ratulangi University and relate the results to their learning outcomes. The data in this study comes from primary data. Learning outcomes are obtained from class data on learning outcomes during the odd semester of the 2022/2023 academic year, while the MBTI personality results are obtained by giving tests available on the official MBTI website. The sampling technique used is purposive sampling. Samples were taken from 6 classes and 3 subjects. This type of research is a quantitative descriptive research. Processing data using descriptive statistical techniques. The results showed that 45.55% of students were introverted and 53.45% were extroverted. The highest number of students in terms of personality groups were Diplomats at 37.50% and at least Analysts at 9.05%. The highest number in terms of personality type was the ENFJ personality type from the Diplomat group at 15.09% and the least ENTP from the Analyst group at 1.29%. For learning outcomes, in terms of personality groups, the highest score was achieved by the Diplomat group with a score of 85.7 and the lowest score was Explorer with a value of 82.75. And the learning outcomes in terms of personality type, the highest score is the ENTP personality type from the Analyst group with a score of 92 and the lowest score is INTP from the Analyst group with a value of 74. The conclusion is that it is very important for an educator to understand the personality of his students. The Diplomat personality group is the most personality group and also has the best learning outcomes. The ENFJ personality type is the most numerous and also has good grades, while the ENTP personality type is the least, but achieves the highest learning outcomes. It is possible for other personality types to be successful in the learning process in accounting majors. In the end, it is necessary to continue to do research on the topic of student personality research.